2009
DOI: 10.1007/s10238-009-0077-6
|View full text |Cite
|
Sign up to set email alerts
|

The significance of E266K polymorphism in the NOD1 gene on Helicobacter Pylori infection: an effective force on pathogenesis?

Abstract: The severity of Helicobacter pylori-related diseases varies greatly among infected individuals and seems to be influenced by both host and bacterial factors. Infection with a cytotoxin-associated gene pathogenicity island (Cag PAI)-positive H. Pylori strain causes a higher grade of gastric mucosal inflammation than an infection caused by a negative strain. Furthermore, such an infection is associated with severe atrophic gastritis and gastric adenocarcinoma. NOD1 protein is a cytosolic pattern recognition rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 55 publications
1
32
1
1
Order By: Relevance
“…It has been reported that the NOD1 G796A mutation increases the risk for gastric mucosal atrophy substantially (OR 34.2 for NOD1 796AA, OR 13.35 for NOD1 796GA vs. NOD1 796GG) [57]. …”
Section: Host Geneticsmentioning
confidence: 99%
“…It has been reported that the NOD1 G796A mutation increases the risk for gastric mucosal atrophy substantially (OR 34.2 for NOD1 796AA, OR 13.35 for NOD1 796GA vs. NOD1 796GG) [57]. …”
Section: Host Geneticsmentioning
confidence: 99%
“…Of note, Boffetta et al [114] proposed that sarcoidosis may be associated with increased CRC and kidney cancer risk, and Ji et al [115] suggested that sarcoidosis may be connected with higher risk of squamous cell carcinoma, melanoma, nonthyroid endocrine tumors, non-Hodgkin lymphoma, and leukemia. In addition, a homozygous variant genotype of rs2075820 was associated with elevated risk of peptic ulcer [116], antral atrophy, antral intestinal metaplasia, and eradication failure [117] in HP-positive patients; it also correlated with increased risk of CD [118]. In 2009, Verma et al [119] showed that the A allele of rs72551113 and the G allele of L370R are associated with increased UC risk, whereas the C allele of rs72551107 is connected with lower UC risk.…”
Section: Nod1/card4 Gene Polymorphisms and Cancer Riskmentioning
confidence: 94%
“…Recent report revealed that the carriage of the NOD1 G796A (E266K) mutation increases the susceptibility for gastric atrophy strikingly: OR = 34.2 in NOD1 796AA and OR = 13.35 in NOD1 796GA compared to subjects with NOD1 796GG (Kara et al, 2010). …”
Section: Nod1mentioning
confidence: 99%
“…PTPN11 G/A at intron3 intron rs2301756 248 Japanese (Goto, 2006a) GG ,GA :0.70,AA :0.09 *GG (59%),GA (49%),AA (11%) " 979 Japanese (Hishida, 2009a) GG ,GA+AA :0.62 ‡ *GG (22%),GA+AA (15%) ‡ NOD1 G796A Non-synonimous (Glu266Lys) rs2075820 150 Turks (Kara, 2010) GG ,GA : 13.35*,AA :34.2* TLR4 A+896G Non-synonimous (Asp299Gly) rs4986790 103 Caucasians (Hold, 2007) AA ,AG :11.0* AA (36%),AG (87%) § " 717 Venezuelan (Kato, 2007) GlyGly/ AspGly,AspAsp : 1.53 TLR4 G+3725C 3'UTR rs11536889 980 Japanese (Hishida, 2009b) GG,GC+CC:1.33 GG(18%),GC+CC(22%) ‡ CD14 C-159T(C-260T) 5'UTR rs2569190 717 Venezuelan (Kato, 2007) CC,CT+TT :1.06…”
Section: Il-4r A398gmentioning
confidence: 99%